Surge [videorecording (Blu-Ray)] - Karia, Aneil; Karia, Aneil; Whishaw, Ben, 1980-; Haddington, Ellie; Gelder, Ian (FilmRise, 2021)
Follows a man who works as an airport security officer as he sets off on a wild and reckless journey through London over the course of twenty-four hours after an impulsive act of rebellion.